Rewriting a Discursive Practice: Atheist Adaptation of Coming Out Discourse. (April 2017) - Cloud, Doug
Coming out is a powerful way for individuals to disclose, constitute, and perform membership in stigmatized identity categories. The practice has now spread far beyond its LGBTQ origins. In this essay, I examine how atheists and other secularists have taken up and adapted coming out discourse to meet their situational and rhetorical needs. Through an analysis of 50 narratives about coming out atheist, I show that atheist writers use coming out discourse to claim both high and low agency over their identities. They both follow and resist a low-agency approach that has sometimes characterized LGBTQ uses of coming out discourse. Furthermore, I argue that the attribution of high personal agency in coming out discourse and other discourses of identity can introduce themes of deliberation, choice, and uncertainty, leading to a richer public discussion of identity category membership.